Nuclear Magnetic Shieldings of Stacked Aromatic and Antiaromatic Molecules - Mera-Adasme, R (American Chemical Society, 2017)
Nuclear magnetic shieldings have been calculated at the density functional theory (DFT) level for stacks of benzene, hexadehydro[12]annulene, dodecadehydro[18]annulene, and hexabenzocoronene. The magnetic shieldings due to the ring currents in the adjacent molecules have been estimated by calculating nucleus independent molecular shieldings for the monomer in the atomic positions of neighbor molecules. The calculations show that the independent shielding model works reasonably well for the 1H NMR shieldings of benzene and hexadehydro[12]annulene, whereas for the larger molecules and for the 13C NMR shieldings the interaction between the molecules leads to shielding effects that are at least of the same size as the ring current contributions from the adjacent molecules. A better agreement is obtained when the nearest neighbors are also considered at full quantum mechanical (QM) level. The calculations suggest that the nearest solvent molecules must be included in the quantum mechanical system, at least when estimating solvent shifts at the molecular mechanics (MM) level. Current density calculations show that the stacking does not significantly affect the ring current strengths of the individual molecules, whereas the shape of the ring current for a single molecule differs from that of the stacked molecules. © 2017 American Chemical Society.